Effects of polyphenolic maqui (Aristotelia chilensis) extract on the inhibition of NLRP3 inflammasome and activation of mast cells in a mouse model of Crohn’s disease-like colitis - Ortiz-Cerda, Tamara; Argüelles-Arias, Federico; Macías-García, Laura; Vázquez-Román, Victoria; Tapia, Gladys; Xie, Kangzhe; García-García, María Desirée; Merinero, Manuel; García-Montes, Josefa-María; Alcudia, Ana; Witting, Paul K.; De-Miguel, Manuel (Frontiers in Immunology, 2024)
Introduction: Crohn’s disease (CD) involves activation of mast cells (MC) and NF-кB in parallel with the PPAR-α/NLRP3 inflammasome/IL-1β pathway in the inflamed colon. Whether polyphenols from maqui (Aristotelia chilensis) represent a natural alternative treatment for CD is unclear. Therefore, we used an animal model of 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced CD-like colitis to investigate protective effects of maqui extract through monitoring NLRP3 inflammasome and MC activation in colon tissue. Methods: Maqui extract was administered via orogastric route to mice after (post-Treatment group) or prior (pre-Treatment group) to TNBS-induction. Colon pathology was characterized by histoarchitectural imaging, disease activity index (DAI), and assessing NF-кB, p-NF-кB, PPAR-α/NLRP3 expression and IL-1β levels. Results: Compared to mice treated with TNBS alone administration of anthocyanin-rich maqui extract improved the DAI, colon histoarchitecture and reduced both colon wet-weight and transmural inflammation. Induction with TNBS significantly increased colonic NLPR3 inflammasome activation, while co-treatment with maqui extract (either post- or pre-Treatment) significantly downregulated NLRP3, ASC and caspase-1 levels, which manifested as reduced colonic IL-1β levels. Supplemented maqui extract marginally diminished NF-кB activity in epithelial cells but reached statistical significance in immune cells (as judged by decreased NF-кB phosphorylation). PPAR-α signaling was largely unaffected by Maqui whereas MC infiltration into the colon mucosa and submucosa decreased and their level of degranulation was suppressed. Conclusion: These outcomes show the post- and pre- Treatment effect of a polyphenolic extract rich in anthocyanins from maqui the acute phase of TNBS- induced CD-like colitis is linked to suppression of the NLRP3 inflammasome and reduced MC responses. These data indicate that maqui extract represents a potential nutraceutical for the treatment of inflammatory bowel disease (IBD).